When movies were theater : architecture, exhibition, and the evolution of American film - Paul, William, 1944- (Film and culture., 2016)
There was a time when seeing a movie meant more than seeing a film. The theater itself shaped the very perception of events onscreen. This multilayered history tells the story of American film through the evolution of theater architecture and the surprisingly varied ways movies were shown, ranging from Edison's 1896 projections to the 1968 Cinerama premiere of Stanley Kubrick's '2001'. The study matches distinct architectural forms to movie styles, showing how cinema's roots in theater influenced business practices, exhibition strategies, and film technologies.